Monitoring Macro-Financial Vulnerability : A Primer - Ghosh, Swati R. (World Bank, Washington, DC, 2016)
Linkages between the real and financial sectors in an economy can lead to a buildup of balance sheet mismatches of key entities—corporates, financial institutions, households, and the public sector. Once such imbalances have built up, they can make the economy vulnerable to macroeconomic shocks, whether external or domestic in origin. This paper discusses the key mismatches that can make entities vulnerable to shocks and how such vulnerability can build up during the business cycle. Against this backdrop, the paper then discusses a framework and potential indicators that may be useful to monitor such developments. These indicators are being developed as part of the MFM macro-financial monitoring effort. The paper is organized as follows. Section two provides a brief discussion of the risks associated with these different balance sheet mismatches. Section three discusses how positive shocks in the real sector—such as an upturn in domestic business cycles (which in turn are often instigated or accompanied by external developments such as capital inflows)—can interact with the financial sector and lead to a build-up of balance sheet mismatches. Section four then describes how, once such vulnerability has been built up, a negative shock can lead to a downward spiral of credit contraction and economic downturns. Finally, section five discusses a possible set of indicators for measuring the buildup of vulnerability.